2007
DOI: 10.1111/j.1478-4408.2007.00101.x
|View full text |Cite
|
Sign up to set email alerts
|

Bordeaux‐R interactions with surfactants: thermochromic investigations of proton ionisation in cationic, nonionic and anionic surfactant solutions

Abstract: Apparent thermodynamic parameters for the hydroxy proton ionisation of Bordeaux‐R were obtained in micellar solutions using the thermochromic method. The effect of addition of the surfactants CTAB, TX‐100 and SDS was investigated in buffered solutions in the pH range of 6–13. Ionisation constants in water and in the presence of surfactants were determined spectrophotometrically and the pK′ of Bordeaux‐R in water was found to be 10.90 in the absence of surfactant. However, at concentrations above critical micel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…We have carried out an extensive literature survey before choosing the concentration of surfactants that are critical for the effective encapsulation of the CDTCM by the titania shell. Based on reference [25], Khamis et al, demonstrated that the CTAB critical micelle concentration (CMC) of 1.0 mM significantly changed the values of the pK acidity constant, the enthalpy, and the entropy of ionization of Bordeaux‐R. In another article, by Javid et al,, 47 the authors demonstrated that the concentration of the CTAB changed the zeta size.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have carried out an extensive literature survey before choosing the concentration of surfactants that are critical for the effective encapsulation of the CDTCM by the titania shell. Based on reference [25], Khamis et al, demonstrated that the CTAB critical micelle concentration (CMC) of 1.0 mM significantly changed the values of the pK acidity constant, the enthalpy, and the entropy of ionization of Bordeaux‐R. In another article, by Javid et al,, 47 the authors demonstrated that the concentration of the CTAB changed the zeta size.…”
Section: Resultsmentioning
confidence: 99%
“…The above references suggest that the concentration affects micelle formation, and that it is better for the concentration of the systems to be above the critical micelle concentration (CMC). Hence, we have chosen to work with only one concentration above the CMC for each surfactant, above 1.0 × 10 −3 mmoleL −1 for the cationic CTAB surfactant, 25 above 3.0 × 10 −3 mmoleL −1 for the anionic SDBS surfactant, 49 and above 0.2 × 10 −3 mmoleL −1 for the non‐ionic hexadecanol surfactant 50 . In addition, we have also tested the various concentrations of the TiO 2 precursor with respect to the fixed amount of the surfactant (eg, TTIP: CTAB), to understand the effective encapsulation of the CDTCM.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation